Stress fractures biblical splints for everyday pressures - Swindoll, Charles R. 1934- (Portland, OR Multnomah, 1990)
Inlcudes bibliographical references.
Keywords: Stress (psychology) -- religious aspects -- Christianity; Christian life -- 1960-